Pengaruh Metode Tilawati Terhadap Kefasihan Membaca Al-Qur’an Santri di Pondok Pesantren Darul Amin Palangka Raya. - Maula, Adam Jordy; Hartati, Zainap; Syahmidi, Syahmidi (Lembaga Dongan Dosen, 2024)
The tilawati method is a method that lies in teaching techniques that focus on talaqqi (listening to direct reading), intensive repetition, and emphasis on tajwid from the early stages. This method is effective for various ages, from children to adults, because it combines visual, auditory, and direct practice elements in learning. In addition, this method usually uses a classical approach with a structured learning duration, allowing students to achieve optimal results in a relatively short time. Research on the Tilawati method aims to see the impact of this method on students' reading and understanding of tajwid, and to assess the effectiveness of the method compared to other methods in the context of learning the Qur'an in Indonesia. The results of the study are expected to provide a positive contribution to the development of Qur'an learning methods in Islamic educational institutions. The research method used is a combination research (mixed method). Combination research is used to collect, analyze, and mix qualitative and quantitative methods. While qualitative research is used to answer the formulation of the problem, namely how to apply the tilawati method in reading the Qur'an at the Darul Amin Islamic Boarding School, while quantitative is used to answer the formulation of the problem, namely whether the tilawati method affects the fluency of students at the Darul Amin Islamic Boarding School. Keywords: Tilawati Method, Al-Quran, Fluency.educator